Fibrinogen as a predictor of bleeding severity after normal delivery and cesarean section - Sara Khashkhashi Moghaddam; Mostafa Ghasempour; Shahriar Norouzpour; Mehrdad Mokarram Dori; negar morovatdar; Sahar Shahbazi; Zohreh Feizi; Naser Naderi; Seyyede Houra Mousavi Vahed; Nahid Zirak (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2024)
Introduction: Postpartum hemorrhage (PPH) is one of the main causes of maternal mortality. The present study was conducted with aim to investigate the relationship between low levels of fibrinogen and the severity of PPH and the importance of administering fibrinogen concentrate or cryo to reduce bleeding.Methods: This prospective cohort study was conducted from 2017 to 2019 on 122 mothers with uterine bleeding in the first 24 hours after delivery in Mashhad. In case of persistent bleeding and rejection of traumatic causes, misoprostol was prescribed, and blood samples were taken at this time (time H0). Patients were divided into severe and non-severe groups by considering the severity of bleeding from H0 to 24 hours. Data were analyzed by SPSS software (version 16) and independent t-test and Mann-Whitney, paired t, Chi-square and Fisher's tests. P<0.05 was considered statistically significant.Results: Of 122 mothers, 38 and 84 were in the severe and non-severe groups, respectively. More than 50% of the mothers had a normal delivery, and there was no significant difference between the two groups in terms of delivery method (p=0.883). Postpartum fibrinogen level in H0 was significantly lower in the severe group compared to the non-severe group (p<0.001). The mean fibrinogen level was 274.8±115.8 mg/dL in the severe and 368.4±78.5 mg/dL in the non-severe groups.Conclusion: Early administration of products containing fibrinogen can help to reduce the amount of bleeding in case of PPH and thus reduce the number of bleeding complications and possible interventions. In future studies along with increasing the sample volume, sampling 12 and 24 hours after delivery is also suggested to control the level of fibrinogen.